Profile of baking industry in Iloilo City - Serviano, Fe B. (2004.)
Businesses like bakeries or bakeshops have become good source of income for entrepreneurs within Iloilo City.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Baking industry; Iloilo City